Transmontano Effect of sex and carcass weight on sensory quality of goat meat of Cabrito Transmontano - Rodrigues, Sandra (2011)
The main purpose of this work was the characterization of Cabrito Transmontana goat kid carcass and meat, which is a Protected Origin Designation product. The effects of sex and carcass weight were studied. Sensory attributes of toughness, juiciness, flavor intensity, flavor quality, odor intensity, fiber presence (stringy), sweet intensity, and overall acceptability were evaluated in 60 males and females allocated to 3 carcass weight groups: 4, 6, and 8 kg. Sensory quality of meat was evaluated by a trained taste panel of 11 experts in 5 sessions. Generalized Procrustes analysis was performed, and 93% of total variability was explained by the 2 first factors (axes). Correlation between sensory traits and factors 1 and 2 allowed the factors to be renamed as toughness/aroma and juiciness/acceptability, respectively. Procrustes analysis indicated that a sex effect was detected by experts. Meat from males presented greater juiciness, flavor quality, and general acceptability than did meat from females. Cabrito Transmontano Protected Origin Designation includes animals from 4 to 9 kg of carcass weight. However, differences among them can be important, because the taste panel found differences between animals from distinct carcass weight ranges. Lighter weight carcasses were considered more tender with less flavor and odor intensity than heavier carcasses.